Hydrogels with Dynamic Biochemical Environment for 3D Cell Culture - Nijsure, Devang (My University, 2018)
The in vivo 3D extracellular matrix provides a temporal regulatory environment of chemical cues. Understanding this dynamic environment will be crucial for efficient drug screening, diseases mechanism elucidation, and tissue engineering. Therefore, in vitro 3D cell culture systems with reversible chemical environments are required. To this end, we developed a non-cytotoxic agarose-desthiobiotin hydrogel to sequester streptavidin biomolecule conjugates (KD 10-11 M), which can then be displaced by the addition of biotin (KD 10-15 M). Streptavidin biomolecule conjugates were simultaneously and sequentially immobilized by changing media components. The time required for biochemical environment exchange was minimized by increasing the surface area to volume ratios and pore size of the hydrogels. We temporally controlled the cell adhesive properties of hydrogels with RGD modified streptavidin to influence endothelial cell tube formation.
Keywords: Hydrogels; Biomaterial; Tissue Engineering; 3D Cell Culture; Dynamic; Extracellular Matrix